Remote teaching: Perception of nursing students about their training process - da Silva, Laísa Ferreira; Lima, Cibelle Ponci Marques; Sakai , Andressa Midori; Silva, Larissa Gutierrez de Carvalho (Seven Editora, 2023)
This article seeks to unveil the perceptions of nursing students regarding the suspension of classroom activities and the insertion of emergency remote learning during the COVID-19 pandemic. This is a qualitative study, carried out with nursing students who experienced remote teaching in their training process; the interviews were collected from March to August 2022. Data analysis was performed using the Collective Subject Discourse methodology. As a result, seven third year undergraduate nursing students from a university in the south of the country participated in the study, all female, aged 21 to 24 years, from the analysis of the collective subject discourse were divided into two categories, between potentialities and weaknesses pointed out in the DCS. The potentialities and weaknesses of the insertion of remote emergency teaching in the perception of the students were raised from this research.DOI:https://doi.org/10.56238/globalhealthprespesc-072